Preparation method and device of fuel cell anode catalyst TaN

By using tantalum pentachloride, cetyl trimethylammonium bromide and urea to prepare TaN catalyst in anhydrous ethanol, the high cost of platinum carbon catalyst and complex process are solved, and the efficient and environmentally friendly fuel cell anode is achieved Catalyst preparation, matches the catalytic efficiency of platinum carbon and reduces production costs.

CN119306185APending Publication Date: 2025-01-14PERIC SPECIAL GASES CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411308130.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing fuel cell anode catalyst material platinum carbon (Pt-C) has high cost, complex production processes and is not environmentally friendly, so it is necessary to seek alternative materials with low cost, high efficiency and environmentally friendly.

Method used

Using tantalum pentachloride as the source of tantalum, the fuel cell anode catalyst is prepared by adding cetyl trimethylammonium bromide and urea to anhydrous ethanol to ultrasonic dissolution to form a TaN precursor, and the heating reaction is raised under the protective gas atmosphere. TaN, control the reaction temperature and temperature change rate to ensure the stability of the catalyst structure.

Benefits of technology

The catalytic efficiency matching the platinum carbon catalyst is achieved, while reducing production costs, simplifying process flow, and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306185A_ABST
    Figure CN119306185A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and device of a fuel cell anode catalyst TaN, and belongs to the technical field of catalyst preparation. Comprising the following steps: S1, adding tantalum pentachloride into absolute ethyl alcohol, then adding hexadecyl trimethyl ammonium bromide for ultrasonic dissolution, then adding urea for ultrasonic dissolution, and finally stirring to obtain a TaN precursor; and S2, reacting the TaN precursor in a protective gas atmosphere to obtain a TaN solid, and grinding and sieving the TaN solid to obtain the catalyst TaN. The tantalum pentachloride is selected as the tantalum source of the fuel cell anode catalyst TaN, so that the production cost is reduced, the production process is simple, and as the electron arrangement of tantalum atoms belongs to transition metal element electron arrangement, the tantalum atoms are easy to accept or give electrons in a chemical reaction, and a more stable compound is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of catalyst preparation, and specifically relates to a method and device for preparing TaN, an anode catalyst for a fuel cell. Background Art

[0002] As the global demand for clean energy grows, the development of fuel cells, as an efficient and environmentally friendly energy conversion device, has attracted attention. Fuel cells are devices that convert chemical energy into electrical energy through redox reactions between hydrogen and oxygen. However, the low efficiency of the anode reaction of fuel cells has seriously restricted the power supply efficiency and the development of fuel cells, giving rise to a series of studies on anode catalyst preparation technologies. The commonly used commercial fuel cell anode catalyst material is platinum carbon (Pt-C), but due to its high cost, seeking low-cost transition metal elements to replace precious metals to prepare efficient anode catalysts has become a hotly researched issue.

[0003] Therefore, many scholars reduce production costs by increasing catalytic efficiency or extending the service life of batteries. The Chinese patent with the announcement number CN113540481B discloses a proton exchange membrane fuel cell platinum cobalt alloy carbon catalyst and its preparation method. The document uses a high-temperature preparation process to alloy platinum elements with cobalt elements to prepare fuel cell alloy catalysts, improves the degree of alloying, reduces the cost of catalysts, improves fuel cell performance and reduces the load of precious metals applied to fuel cell cells, but the post-processing process of the catalyst is complicated, involving more chemicals, and increases production costs. The Chinese patent with the announcement number CN109841857A discloses a preparation method of a fuel cell catalyst mesoporous Pt / C, which uses a phenolic resin and a block copolymer prepared from phenolic compounds and formaldehyde to prepare mesoporous carbon through steps such as reaction and calcination, and then loads a metal precursor and reduces the mesoporous Pt / C catalyst through a reducing agent. Although the preparation process of this method is simple and improves the catalytic effect, it uses a large amount of organic reagents, is environmentally unfriendly, and is relatively complicated in the subsequent anhydrous treatment process.

[0004] Therefore, it is an urgent problem to study a kind of anode catalyst material that can replace platinum carbon (Pt-C) without reducing the catalytic efficiency, reducing the production cost, simplifying the production process and being environmentally friendly. Summary of the invention

[0005] In view of the technical problem of high cost of platinum-carbon (Pt-C) anode catalyst materials in the prior art, the present application proposes a method and device for preparing a fuel cell anode catalyst TaN.

[0006] The technical solution of this application is as follows:

[0007] On the one hand, the present application provides a method for preparing a fuel cell anode catalyst TaN, comprising the following steps:

[0008] Step S1. Add tantalum pentachloride to anhydrous ethanol, then add hexadecyltrimethylammonium bromide and ultrasonically dissolve it, then add urea and ultrasonically dissolve it, and finally stir to obtain a TaN precursor;

[0009] Step S2: reacting a TaN precursor under a protective gas atmosphere to obtain a TaN solid, and grinding and sieving the TaN solid to obtain a catalyst TaN.

[0010] Preferably, in step S1, the ratio of tantalum pentachloride, urea, hexadecyltrimethylammonium bromide and anhydrous ethanol is (1-1.5) g: (3-6) g: (5-10) g: (50-70) mL; and the stirring time is 3-6 h.

[0011] Preferably, in step S1, the ratio of tantalum pentachloride, urea, hexadecyltrimethylammonium bromide and anhydrous ethanol is 1.2 g: (4-5) g: (6-8) g: (60-70) mL; and the stirring time is 4-5 h.

[0012] Preferably, in step S1, the purity of tantalum pentachloride is greater than 99.9%, the purity of urea is greater than 96%, and the purity of hexadecyltrimethylammonium bromide is greater than 96%.

[0013] Preferably, in step S2, the protective gas is any one of nitrogen, argon or helium, the flow rate of the protective gas is 0.2-1 L / min, and the purity of the protective gas is greater than 99.999%.

[0014] Preferably, in step S2, the protective gas is nitrogen, the flow rate of the protective gas is 0.2-1 L / min, and the purity of the protective gas is greater than 99.999%.

[0015] Preferably, the reaction process in step S2 is to heat up to 800-1000° C. for 2-5 hours, then keep warm for 2-3 hours, and cool down to 25° C. for 2-5 hours.

[0016] Preferably, the reaction process in step S2 is to heat up to 800-850° C. for 3-4 hours, then keep warm for 2-3 hours, and cool down to 25° C. for 2-5 hours.

[0017] On the other hand, the present application provides a device for preparing a fuel cell anode catalyst TaN, including a quartz tube, wherein a porcelain boat is placed in advance inside the quartz tube; the porcelain boat is used to place a TaN precursor; the porcelain boat is formed by buckling an upper porcelain boat and a lower porcelain boat; the TaN precursor is located in the lower porcelain boat; a protective gas inlet is provided at one end of the quartz tube, and a protective gas outlet is provided at the other end.

[0018] Beneficial effects of this application:

[0019] The present application uses tantalum pentachloride as the tantalum source of the fuel cell anode catalyst TaN. On the one hand, the price of tantalum pentachloride is relatively cheap compared to platinum carbon. On the other hand, the electronic configuration of tantalum atoms belongs to the electronic configuration of transition metal elements, with unfilled d orbitals and s orbitals, which makes it easy to accept or give electrons in certain chemical reactions to form more stable compounds. The tantalum atoms in tantalum pentachloride are located at the center of the octahedron, and are coordinated by chlorine atoms to form a stable structure. This structure is easy to become unstable at high temperatures, thereby initiating chemical reactions. The melting point (221°C) and boiling point (242°C) of tantalum pentachloride are relatively low, so it is easy to reach the temperature range required for the reaction under heating conditions, thereby accelerating the reaction rate. The present application uses anhydrous ethanol as a solvent, and adds tantalum pentachloride hexadecyltrimethylammonium bromide and urea in sequence, and ultrasonically dissolves each time a substance is added to accelerate the dissolution of the substance, and finally stirs to obtain a TaN precursor gel. The present application reasonably controls the reaction temperature in the preparation of the catalyst TaN, and controls the rate of temperature change during the heating process and the cooling process, so as to avoid the catalyst structure being destroyed under rapid temperature changes. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Attached Figure 1 Schematic diagram of the reaction device of this application.

[0021] Figure numerals: 1, quartz tube; 2, protective gas inlet; 3, lower porcelain boat; 4, upper porcelain boat; 5, protective gas outlet. DETAILED DESCRIPTION

[0022] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.

[0023] This embodiment provides a method for preparing a fuel cell anode catalyst TaN. It should be noted that the anhydrous ethanol, tantalum pentachloride, hexadecyltrimethylammonium bromide and urea required in this embodiment are all commercially available, wherein the purity of tantalum chloride is 99.99%, the purity of hexadecyltrimethylammonium bromide is 98.5%, and the purity of urea is 98%. The specific steps are as follows:

[0024] Step S1. Add 60 mL of anhydrous ethanol to a 150 mL beaker, weigh 1.2 g of tantalum pentachloride, add it and ultrasonicate until it is dissolved, then add 7 g of hexadecyltrimethylammonium bromide and ultrasonicate until it is dissolved, then add 4.5 g of urea and ultrasonicate until it is dissolved, put a rotor into the beaker, and finally cover it with plastic wrap, poke holes in the plastic wrap with a toothpick, and stir at a speed of 50 r / min to obtain a gel-like TaN precursor;

[0025] Step S2. Transfer the gel-like TaN precursor to the lower porcelain boat 3, cover it with the upper porcelain boat 4, which serves as a buffer and protective gas purge, and move the porcelain boat to the quartz tube 1 in the tubular furnace, introduce nitrogen with a purity greater than 99.999% through the protective gas inlet 2, control the gas flow rate to 0.5L / min, and discharge the protective gas through the protective gas outlet 5. Heat the quartz tube 1 in the tubular furnace for 5 hours to 850°C, then keep it warm for 2 hours, and cool it down to 25°C for 5 hours.

[0026] Example 2

[0027] This embodiment provides a method for preparing a fuel cell anode catalyst TaN. It should be noted that the anhydrous ethanol, tantalum pentachloride, hexadecyltrimethylammonium bromide and urea required in this embodiment are all commercially available, wherein the purity of tantalum chloride is 99.99%, the purity of hexadecyltrimethylammonium bromide is 98.5%, and the purity of urea is 98%. The specific steps are as follows:

[0028] Step S1. Add 50 mL of anhydrous ethanol to a 150 mL beaker, weigh 1.5 g of tantalum pentachloride, add it and ultrasonicate until it is dissolved, then add 5 g of hexadecyltrimethylammonium bromide and ultrasonicate until it is dissolved, then add 6 g of urea and ultrasonicate until it is dissolved, put a rotor into the beaker, and finally cover it with plastic wrap, poke holes in the plastic wrap with a toothpick, and stir at a speed of 50 r / min to obtain a gel-like TaN precursor;

[0029] Step S2. Transfer the gel-like TaN precursor to the lower porcelain boat 3, cover it with the upper porcelain boat 4, which serves as a buffer and protective gas purge, and move the porcelain boat to the quartz tube 1 in the tubular furnace, introduce argon gas with a purity greater than 99.999% through the protective gas inlet 2, control the gas flow rate to 1L / min, and discharge the protective gas through the protective gas outlet 5. Heat the quartz tube 1 in the tubular furnace for 4 hours to 800°C, then keep it warm for 3 hours, and cool it down to 25°C for 4 hours.

[0030] Example 3

[0031] This embodiment provides a method for preparing a fuel cell anode catalyst TaN. It should be noted that the anhydrous ethanol, tantalum pentachloride, hexadecyltrimethylammonium bromide and urea required in this embodiment are all commercially available, wherein the purity of tantalum chloride is 99.99%, the purity of hexadecyltrimethylammonium bromide is 98.5%, and the purity of urea is 98%. The specific steps are as follows:

[0032] Step S1. Add 70 mL of anhydrous ethanol to a 150 mL beaker, weigh 1 g of tantalum pentachloride, add it and ultrasonicate until it is dissolved, then add 10 g of hexadecyltrimethylammonium bromide and ultrasonicate until it is dissolved, then add 3 g of urea and ultrasonicate until it is dissolved, put a rotor into the beaker, and finally cover it with plastic wrap, poke holes in the plastic wrap with a toothpick, and stir at a speed of 50 r / min to obtain a gel-like TaN precursor;

[0033] Step S2. Transfer the gel-like TaN precursor to the lower porcelain boat 3, cover it with the upper porcelain boat 4, which serves as a buffer and protective gas purge, and move the porcelain boat to the quartz tube 1 in the tubular furnace, introduce nitrogen with a purity greater than 99.999% through the protective gas inlet 2, control the gas flow rate to 0.8L / min, and discharge the protective gas through the protective gas outlet 5. Heat the quartz tube 1 in the tubular furnace for 2 hours to 850°C, then keep it warm for 3 hours, and cool it down to 25°C for 2 hours.

[0034] Example 4

[0035] This embodiment provides a method for preparing a fuel cell anode catalyst TaN. It should be noted that the anhydrous ethanol, tantalum pentachloride, hexadecyltrimethylammonium bromide and urea required in this embodiment are all commercially available, wherein the purity of tantalum chloride is 99.99%, the purity of hexadecyltrimethylammonium bromide is 98.5%, and the purity of urea is 98%. The specific steps are as follows:

[0036] Step S1. Add 55 mL of anhydrous ethanol to a 150 mL beaker, weigh 1.3 g of tantalum pentachloride, add it and ultrasonicate until it is dissolved, then add 8 g of hexadecyltrimethylammonium bromide and ultrasonicate until it is dissolved, then add 4 g of urea and ultrasonicate until it is dissolved, put a rotor into the beaker, and finally cover it with plastic wrap, poke holes in the plastic wrap with a toothpick, and stir at a speed of 50 r / min to obtain a gel-like TaN precursor;

[0037] Step S2. Transfer the gel-like TaN precursor to the lower porcelain boat 3, cover it with the upper porcelain boat 4, which serves as a buffer and protective gas purge, and move the porcelain boat to the quartz tube 1 in the tubular furnace, introduce helium with a purity greater than 99.999% through the protective gas inlet 2, control the gas flow rate to 0.2L / min, and discharge the protective gas through the protective gas outlet 5. Heat the quartz tube 1 in the tubular furnace for 3 hours to 1000°C, then keep it warm for 3 hours, and cool it down to 25°C for 3 hours.

[0038] Comparative Example 1

[0039] The difference between this comparative example and Example 1 is that the heating temperature of this example is 500°C.

[0040] Comparative Example 2

[0041] The difference between this comparative example and Example 1 is that the heating temperature of this example is 1200°C.

[0042] Comparative Example 3

[0043] The difference between this comparative example and Example 1 is that the heating time of this example is 1 hour.

[0044] Comparative Example 4

[0045] The catalyst platinum carbon in this comparative example was purchased from the market.

[0046] Performance Testing

[0047] The finished catalyst TaN products obtained in Examples 1 to 4 and the finished catalyst products of Comparative Examples 1 to 4 were ground into powders, and the half-wave potential of the catalysts was detected by an electrochemical workstation. The results are shown in Table 1. In the field of electrochemistry, the half-wave potential usually refers to the potential value when the redox reaction is halfway through the electrochemical cyclic voltammetry experiment, which is represented by E1 / 2. This parameter is often used to evaluate the activity of the catalyst because it reflects the electrochemical performance of the catalyst under specific reaction conditions.

[0048] Table 1

[0049] sample Half-wave potential Example 1 0.85V Example 2 0.83V Example 3 0.84V Example 4 0.83V Comparative Example 1 0.75V Comparative Example 2 0.69V Comparative Example 3 0.71V Comparative Example 4 0.84V

[0050] Results Analysis

[0051] In combination with Examples 1 to 4 and Comparative Examples 1 to 4, it can be seen that the half-wave potential of the catalyst TaN prepared by the method of the present application is equivalent to the half-wave potential of the catalyst platinum carbon, wherein the effect of Example 1 is the best, and the half-wave potential is 0.85, which is higher than the half-wave potential of the catalyst platinum carbon purchased in Comparative Example 4. This may be because the electronic configuration of the tantalum atom belongs to the electronic configuration of the transition metal element, with unfilled d orbitals and s orbitals, which makes it easy to accept or give electrons in certain chemical reactions to form more stable compounds. The tantalum atom in tantalum pentachloride is located at the center of the octahedron, and is coordinated by chlorine atoms to form a stable structure. This structure is easy to become unstable at high temperatures, thereby initiating chemical reactions, and the present application reasonably controls the reaction temperature in the preparation of the catalyst TaN, and controls the rate of temperature change during the heating process and the cooling process, which can avoid the catalyst structure from being destroyed under a sharp change in temperature. However, the half-wave potential of the catalyst TaN prepared in Comparative Examples 1 to 3 is lower than the half-wave unit of the catalyst of Examples 1 to 4 and Comparative Example 4. This may be because the temperature or heating rate of the reaction is changed, resulting in a decrease in the activity of the reactants or a change in the crystal structure of the reaction product, resulting in a decrease in the half-wave potential.

[0052] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a fuel cell anode catalyst TaN, characterized in that: The steps include: Step S1. Add tantalum pentachloride to anhydrous ethanol, then add hexadecyltrimethylammonium bromide and ultrasonically dissolve it, then add urea and ultrasonically dissolve it, and finally stir to obtain a TaN precursor; Step S2: reacting a TaN precursor under a protective gas atmosphere to obtain a TaN solid, and grinding and sieving the TaN solid to obtain a catalyst TaN.

2. The method for preparing a fuel cell anode catalyst TaN according to claim 1, characterized in that: In step S1, the ratio of tantalum pentachloride, urea, hexadecyltrimethylammonium bromide and anhydrous ethanol is (1-1.5) g: (3-6) g: (5-10) g: (50-70) mL; and the stirring time is 3-6 h.

3. The method for preparing a fuel cell anode catalyst TaN according to claim 1, characterized in that: In step S1, the purity of tantalum pentachloride is greater than 99.9%, the purity of urea is greater than 96%, and the purity of hexadecyltrimethylammonium bromide is greater than 96%.

4. The method for preparing a fuel cell anode catalyst TaN according to claim 1, characterized in that: In step S2, the protective gas is any one of nitrogen, argon or helium, the flow rate of the protective gas is 0.2-1 L / min, and the purity of the protective gas is greater than 99.999%.

5. The method for preparing a fuel cell anode catalyst TaN according to claim 1, characterized in that: The reaction process in step S2 is to heat up to 800-1000° C. for 2-5 hours, then keep the temperature for 2-3 hours, and cool down to 25° C. for 2-5 hours.

6. The device used in the method for preparing TaN as a fuel cell anode catalyst according to any one of claims 1 to 5, characterized in that: The invention comprises a quartz tube (1), wherein a porcelain boat is placed in advance inside the quartz tube (1); the porcelain boat is used to place a TaN precursor; the porcelain boat is formed by buckling an upper porcelain boat (4) and a lower porcelain boat (3); the TaN precursor is located in the lower porcelain boat (3); a protective gas inlet (2) is provided at one end of the quartz tube (1), and a protective gas outlet (5) is provided at the other end.

Citation Information

Patent Citations

  • Preparation method of meso-porous Pt / C fuel cell catalyst

    CN109841857A

  • A platinum-cobalt alloy carbon catalyst for proton exchange membrane fuel cells and its preparation method

    CN113540481B